Child and Adolescent Psychiatry Outpatient Clinic Referrals During Covid-19 Pandemic in Turkey - ERDOĞDU, AYŞE BURCU (My University, 2022)
© 2022, AVES. All rights reserved.Background: The objective of the current study was to assess how the coronavirus disease 2019 pandemic has affected mental health services compared to the same period of the year before the pandemic. Methods: The data in the study were retrieved from the databases of the computer systems of the hospitals. All referrals in the child psychiatry outpatient clinic between March 1 and June 30, 2019, and between March 1 and June 30, 2020, constituted the sample. Results: Of the 3110 referrals, 2246 were cases and 864 were repeating examinations. Of the 2246 cases, 70.5% (n = 1583) were admitted in 2019, while 29.5% (n = 663) were admitted in 2020. Of the cases who referred in 2019, 37.3% (n = 590) were female, while this rate was 43.9% (n = 291) in 2020. The mean age of 2019 cases was found to be 9.51 ± 4.17, while the mean age of 2020 cases was found to be 10.39 ± 4.06. While attention-deficit hyperactivity disorder, oppositional defiant disorder, conduct disorder, depressive disorder, panic disorder, school refusal, and sleep disorder rates increased significantly, specific learning disorders and mental retardation rates were found to be on the decrease in 2020. In 2019, 47.6% (n = 754) of the cases were followed with medication, and in 2020, this rate increased to 63.2% (n = 419). Conclusion: Pandemic conditions affected the content of public hospital psychiatry referrals significantly. It can be thought that the significant decrease in the number of referrals may be the result of citizens obeying the prohibitions and the fear of disease transmission in families with the onset of the pandemic that precedes the existing psychiatric problems of children.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Psikiyatri; Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); PSYCHIATRY; PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Psikiyatri ve Ruh Sağlığı; Farmakoloji (tıbbi); Psychiatry and Mental Health; Pharmacology (medical); Child psychiatry; referrals; COVID-19 pandemic; MANAGEMENT; ADHD